2021
DOI: 10.7554/elife.61453
|View full text |Cite
|
Sign up to set email alerts
|

The metal cofactor zinc and interacting membranes modulate SOD1 conformation-aggregation landscape in an in vitro ALS model

Abstract: Aggregation of Cu-Zn superoxide dismutase (SOD1) is implicated in the motor neuron disease, ALS. Although more than 140 disease mutations of SOD1 are available, their stability or aggregation behaviors in membrane environment are not correlated with disease pathophysiology. Here, we use multiple mutational variants of SOD1 to show that the absence of Zn, and not Cu, significantly impacts membrane attachment of SOD1 through two loop regions facilitating aggregation driven by lipid induced conformational changes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 79 publications
1
22
0
Order By: Relevance
“…Cytochrome P450–mediated hydroxylation associated with 2,3-aryl migration of the B ring in 2S flavanones forms a 2-hydroxyisoflavanone using IFS ( Figure 4 ). Then, this is dehydrated into the isoflavones (genistein and daidzein) through the natural reaction catalyzed by specific dehydratase enzyme ( Kochs and Grisebach, 1986 ; Hakamatsuka et al, 1990 , 1998 ).…”
Section: Isoflavone Biosynthesis and The Role Of Biosynthetic Genesmentioning
confidence: 99%
“…Cytochrome P450–mediated hydroxylation associated with 2,3-aryl migration of the B ring in 2S flavanones forms a 2-hydroxyisoflavanone using IFS ( Figure 4 ). Then, this is dehydrated into the isoflavones (genistein and daidzein) through the natural reaction catalyzed by specific dehydratase enzyme ( Kochs and Grisebach, 1986 ; Hakamatsuka et al, 1990 , 1998 ).…”
Section: Isoflavone Biosynthesis and The Role Of Biosynthetic Genesmentioning
confidence: 99%
“…In addition to the new compounds, two previously reported bisabolane sesquiterpenes 2 and 3, a phthalide derivative 6, and a chromone 7, were also isolated from this fungal strain. Based on detailed spectroscopic analysis as well as by comparisons with literature data, their structures were identified as hydroxysydonic acid (2) ( Hamasaki et al, 1978 ), sydowic acid (3) ( Hamasaki et al, 1975 ), rubralide C (6) ( Kimura et al, 2007 ), and 2,5-dimethyl-7-hydroxychromone (7) ( Kashiwada et al, 1984 ).…”
Section: Resultsmentioning
confidence: 99%
“…Iguchi and coworkers demonstrated that BPA, injected into the mouse mother’s body (single s.c. injection), was transferred to the brains of fetus within 1 h via going through the immature blood-brain barrier ( Uchida et al, 2002 ). In contrast to the efficient detoxification of endocrine disrupters, such as BPA in the liver, detoxification in the brain may be less efficient due to the low level of drug-metabolizing enzymes in the brain ( Miksys and Tyndale, 2002 ; Miksys et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Upon perinatal exposure to BPA, BPA can penetrate much more easily into the brain of embryo and fetus where the blood-brain barrier is not completely developed ( Uchida et al, 2002 ). The detoxification of BPA in the brain is probably very weak due to the extremely low level of drug-metabolizing enzymes in the brain ( Miksys and Tyndale, 2002 ; Kishimoto et al, 2004 ; Chinta et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%